حق ضحية الجريمة في حماية حياته الخاصة من طرف الضبطية القضائية - رواحنــــة, ناديـــــة (revue mofakir, 2018)
إن من أهم حقوق ضحية الجريمة في مرحلة البحث والتحري هو حماية حياته الخاصة من قبل جهاز الضبطية القضائية باعتباره أول متصل بالدعوى العمومية من خلال تقديم الشكوى من قبل الضحية أو عند القيام بإجراءات البحث والتحري وخاصة على مستوى مسرح الجريمة، فيتعين على الضبطية القضائية في الحالتين أن تعمل على كتم أسرار الضحية والحفاظ على خصوصياتها من خلال سرية التحقيق في مواجهة الجمهور، وكذلك ضرورة إبعاد رجال الإعلام الذين يكون لهم دور بارز في الكشف عن أسرار الأفراد وخاصة في بعض الجرائم أين يجعلون تلك الأسرار مادة إعلامية هامة للتسويق والربح التجاري دون مراعاة لمشاعر وأحاسيس الضحايا.   Abstract: One of the most important rights of the crime victim, during the period of the enquiry, is protecting his/her private life by the Judicial Police which is considered as the first one to get in touch with the public action; either by presenting a complaint of the victim or conducting an enquiry particularly on the crime scene. In the both of the cases, the judicial police should keep the victim’s secrets, protect his/her privacy by conducting an enquiry away from the public, as well as keeping away the media which play an important role in revealing the individuals’ secrets, especially in some crimes in which they make those secrets an important journalistic content for sale and commercial gain, at the expense of the victims feelings.